2015
DOI: 10.1007/s13277-015-4724-0
|View full text |Cite
|
Sign up to set email alerts
|

Fusobacterium nucleatum, inflammation, and immunity: the fire within human gut

Abstract: Fusobacterium nucleatum is an identified proinflammatory autochthonous bacterium implicated in human colorectal cancer. It is also abundantly found in patients suffering from chronic gut inflammation (inflammatory bowel disease), consequently contributing to the pathogenesis of colorectal cancer. Majority of the studies have reported that colorectal tumors/colorectal adenocarcinomas are highly enriched with F. nucleatum compared to noninvolved adjacent colonic tissue. During the course of multistep development… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
81
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(87 citation statements)
references
References 43 publications
5
81
0
1
Order By: Relevance
“…Many studies have also reported that F . nucleatum induced proinflammatory cytokines through different pathways [1920]. However, in the present study, it is first proposed that TLR2/TLR4 regulate F .…”
Section: Discussionmentioning
confidence: 69%
“…Many studies have also reported that F . nucleatum induced proinflammatory cytokines through different pathways [1920]. However, in the present study, it is first proposed that TLR2/TLR4 regulate F .…”
Section: Discussionmentioning
confidence: 69%
“…nucleatum infection could induce inflammation in different cells, including gingival epithelial cells and macrophage [2627]. To clarify the role of F .…”
Section: Resultsmentioning
confidence: 99%
“…F. nucleatum can also be isolated from extra-oral infections and has been associated with inflammatory bowel disease and colorectal cancer11121314. In a previous study24, we used a macrophage model to show that tea polyphenols, including EGCG and theaflavins, can attenuate the inflammatory response induced by F. nucleatum .…”
Section: Discussionmentioning
confidence: 99%
“…F. nucleatum is also a common resident of the human gastrointestinal tract12. Over the past few years, several studies have shown that this bacterial species increases in numbers in patients affected with inflammatory bowel disease and may contribute to the pathogenesis of colorectal cancer121314.…”
mentioning
confidence: 99%